Learner innovativeness, course interaction, and the use of a new educational technology system after the COVID-19 pandemic - Kang, Dongsuk; Park, Min Jae (International Journal of Management Education, 2023)
Due to the global COVID-19 pandemic and social distancing policies, higher education has adopted a new online learning system (e.g., viewing recorded lectures at one's own pace or participating in online streaming courses) as a necessary education service. Although many universities have switched to face-to-face courses in light of the reduced spread of the coronavirus, the new system could be a meaningful complement to the traditional learning method. This study focuses on identifying factors that influence students' utilization of new lecture systems in universities. This research investigated undergraduates majoring in management and other fields in South Korea through structural questionnaires. It analyzes the data using the partial least squares methodology of structural equation analysis. The results show that learners' innovativeness could increase their willingness to use the system, and the learning interaction in a course could improve students' learning satisfaction. Furthermore, the innovativeness could lead to a positive relationship between learning satisfaction, intention to use, and the system's potential impact. These findings suggest that instructors and universities need to offer new opportunities to promote students' willingness and motivation, as well as their preparation for online courses and learning interactions.
Keywords: Blended learning; Educational innovation; Educational management; Learner innovativeness; Learning interaction